Morphological and functional features of the thymus of rats of different age periods in health and at experimental immunostimulation. - Bobrysheva, I. V. (Морфологія / Morphologia / Morfologìâ, 2013)
Background. Data on the structure of the thymus of white rats with experimental immunostimulation in age aspect presented only in a few publications. Objective. Morphofunctional features of the thymus of white male rats of three age periods: pubertal, reproductive and of expressed age-related changes, administered immunomodulator imunofan were studied. Methods. Features of the histological structure of the thymus were studied using an image analyzer based on microscope Olympus CX-41. Areas of subcapsular zone, the cortex and medulla, the total number of cells, lymphocytes and epitelioreticular cells conditional on a standard area (104 μm2) were determined; limphoepitelial index was calculated. Results. The thymus has specific morphological features of the structure in each age group of animals. The thymus of rats of pubertal period has the highest morphometric parameters which somewhat decreased in animals of reproductive period. Animals with expressed age-related changes have signs of age involution of the thymus (replacing of parenchyme of the organ by adipose and connective tissue, a sharp decline in morphometric parameters of morphofunctional zones). Conclusion. Application of imunofan causes unidirectional positive changes of morphometric parameters of the thymus in the rats of all age periods on 7-60 day of observation. In animals of the reproductive period and the period of expressed age-related changes injections of immunomodulator cause a decrease in the intensity of the involutive processes in the thymus.